Public and private returns to investing in nutrition - Alderman, Harold; Sahn, David E. (Oxford University Press, 2016)
The authors examine the impact of nutrition on productivity at both the micro and macro levels and conclude that large economic returns to investing in nutrition. These can be measured at both the individual level as well as through economy-wide indicators such as aggregate incomes and gross domestic product. The evidence comes from a range of methodologies and disciplines, including the work of economic historians, cross-country models, microsimulation, and structural and experimental microeconomic analysis. The positive economic returns to investing in nutrition operate through multiple channels. These range from literature that shows that in utero and early-life nutritional inputs contribute positively to various economic metrics through a range of mediating factors (such as increased stature, improved cognition, and savings associated with reduced morbidity and mortality across the life course) to evidence from long-term historical studies that improved nutrition contributes to large improvements in per capita growth.